In vitro plant regeneration and RAPD assessment of somaclonal variations in safed musli (Chlorophytum borivilianum Santapau & R.R.Fernandes) - Kemat, Nurashikin (2012)
Safed musli (Chlorophytum borivilianum), is a traditional medicinal plant which belongs to liliaceae family and has an increasing demand due to its wide range of uses. It has an aphrodisiac property and form an important ingredient of herbal tonics prescribed in the Ayurvedic systems of medicine. Due to its medicinal properties and high demand in herbal industry, Safed musli has been introduced in Malaysia by Felda in 2008 under Felda Herbal Corporation Sdn. Bhd. The major constraint in the cultivation of Safed musli is long tuber dormancy at about 6 -7 months, so it’s only one crop per year can be grown. Besides, the other constraints include shortage of quality planting material, lower tuber multiplication rate and impossible to obtain true to type and disease free plants either from seed tuber or seed. A study was carried out using in vitro propagation and molecular characterization of Safed musli. In vitro culture has shown the advantage over the conventional methods of vegetative production as it ensures rapid rate of multiplication and disease free abundant plantlets. Young shoot buds of Safed musli were collected and sterilized. 100% of clean culture and plant survived in sterilization ent with 70% alcohol (6 minutes), 50% Sodium hypochlorite (20 minutes), 0.1% aqueous mercuric chloride (15 minutes). Mass production of shoots was achieved on MS medium supplemented with 3 mg/L BAP which produced the highest mean number of shoots (18.9) and shoot length (6.0) cm. MS medium supplemented with 1 mg/L IBA which produced the highest mean number of roots (52.4) and root length (6.6) cm. In acclimatization, plantlets on media containing vermiculite : organic matter (1:1) showed the highest percentage of survival plants (83%) and mean number of shoot length (18.69) cm. Callus of Safed musli were induced from young shoot bud on MS medium containing 5 mg/L 2,4-D with the highest percentage of callus formation (66.66%) and mean weight of callus (10.65) g. For shoot regeneration, the highest percentage (66.67%) and the highest mean number of shoots per vial (9.6) was obtained on MS medium with 0.5 mg/L BAP . The RAPD assessment of somaclonal variations among Safed musli plantlet was performed. Out of 90 bands, 55 were polymorphic bands and 35 were monomorphic bands ranging between 115.43bp – 3388.24bp. RAPD marker effectively recognized the genetic difference among the in vitro shoot.